One size does not fit all: The impact of primary vaccine container size on vaccine distribution and delivery. Issue 28 (22nd June 2015) - Haidari, Leila A.; Wahl, Brian; Brown, Shawn T.; Privor-Dumm, Lois; Wallman-Stokes, Cecily; Gorham, Katie; Connor, Diana L.; Wateska, Angela R.; Schreiber, Benjamin; Dicko, Hamadou; Jaillard, Philippe; Avella, Melanie; et al.
Highlights: Primary container size affects many aspects of vaccine delivery and administration. We used HERMES to simulate different primary vaccine containers in the Benin WHO EPI. The ideal choice for vaccine administration may not be optimal for the whole system. Deviation from vial opening policies may impact the optimal vial size. The optimal vial size may be different for various locations within the same country. Abstract: Background: While the size and type of a vaccine container (i.e., primary container) can have many implications on the safety and convenience of a vaccination session, another important but potentially overlooked consideration is how the design of the primary container may affect the distribution of the vaccine, its resulting cost, and whether the vial is ultimately opened. Methods: Using our HERMES software platform, we developed a simulation model of the World Health Organization Expanded Program on Immunization supply chain for the Republic of Benin and used the model to explore the effects of different primary containers for various vaccine antigens. Results: Replacing vaccines with presentations containing fewer doses per vial reduced vaccine availability (proportion of people arriving for vaccines who are successfully immunized) by as much as 13% (from 73% at baseline) and raised logistics costs by up to 0.06 per dose administered (from 0.25 at baseline) due to increased bottlenecks, while reducing total costs by as much as 0.15 per dose administered (from 2.52 at baseline) due to lower open vial wastage. Primary containers with a greater number of doses per vial each improved vaccine availability by 19% and reduced logistics costs by 0.05 per dose administered, while reducing the total costs by up to 0.25 per dose administered. Changes in supply chain performance were more extreme in departments with greater constraints. Implementing a vial opening threshold reversed the direction of many of these effects. Conclusions: Our results show that one size may not fit all when choosing a primary vaccine container. Rather, the choice depends on characteristics of the vaccine, the vaccine supply chain, immunization session size, and goals of decision makers. In fact, the optimal vial size may vary among locations within a country. Simulation modeling can help identify tailored approaches to improve availability and efficiency.